Pengaruh Keragaman Produk Terhadap Keputusan Pembelian Pada Vierra Oleh-Oleh Kota Pekanbaru - Nurul Ilmi; Rosmayani Rosmayani (SYNERGY: Jurnal Bisnis dan Manajemen, 2023)
The purpose  of this study was to analyze, know and explain  the effect of product  diversity  on purchasing decisions at Viera Souvenirs in Pekanbaru City. This research uses quantitative methods by processing the data obtained from the population and research sample of 100 respondents. The type and source of data used in this research is using secondary   data  and  primary   data  where  data  collection  is  through  distributing  questionnaires  and  conducting interviews.  Then  from  the  data  that  has  been  collected  the authors identify and classify the data using  descriptive analysis methods, namely conducting research from data that has been found in the field. From the results of the study, it was obtained that the product diversity variable was in the strongly agree category, and the purchase decision variable was in the strongly agree category. Then from statistical calculations  there are results where product  diversity  has a significant effect on purchasing decisions at Viera Souvenirs in Pek anbaru City.